ESTIMATION OF THE VALUE OF OIL LOSS DURING THE SEALING OF THE LINEAR PART OF THE PIPELINE - Bolonny, V. T. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
The characteristics of the oil transportation system of Ukraine are presented, the emergency risks of domestic oil transportation pipeline systems are established. The analysis of the accident rate of oil pipeline transport in Ukraine was carried out. The technique for estimating emergency oil leakages in the main pipeline depending on the energy characteristics of the fluid flow and changes in its level in the cross section is developed allowing to determine the volume of oil leakages into the environment from the detection of pressure drop to the establishment of stationary conditions of the pipeline operation and its final stop for the purpose of carrying out repairs. Based on the results of the calculations, the graphs which demonstrate the nature of the formation of soil pollution area by leakage from the pipeline are constructed. The linear part of the main oil pipelines is the most dangerous object, as all emergency situations are associated with emergency processes of different intensity in the form of oil leakage into the environment and in fact are dangerous when system failures appear. The process and the time period for the formation of the ecological danger zone depend on the amount of oil leakage, its intensity. Emergency leakages of oil and petroleum products from pipelines enter the environment, which is often the soil, forming an area of gassiness, and then reach the surface, polluting the atmosphere.